Knowledge Management and Recovery Processes using IT: An approach towards Data Mining. - Nisha, R (International Journal of Supply Chain Management, 2018)
Knowledge Management is a procedure of creating, disseminating, utilizing and handling the data and information of organizations. Knowledge management and recovery process includes innovative design, or it’s exclusively a meeting point on knowledge transferring, storage, and expansion. It indicates multidisciplinary approach for achieving organizational objectives by making the finest utilization of knowledge. For past two decades it has been seen that there is an emerging attention towards knowledge management recovery practices with the usage of information technology. The research paper provides a clear input of knowledge management and recovery process using IT proficiency and its approach towards Data mining; hence data mining is also a tool of business intelligence for knowledge management and recovery process. Key Words: Knowledge management, IT competency, Data Mining,  Knowledge recovery, Data mining